Modification of Calgary Cambridge for Indonesian medical students: Communication guidelines - Galih Cahya Wijayanti; Rizma Adlia Syakurah; Mariatul Fadilah (International Journal of Public Health Science (IJPHS), 2021)
Effective communication skill applied by doctors in the doctor-patient consultation process becomes one of important factors that can improve the consultation outcomes such as patient satisfaction, adherence to treatment and recovery process. However, effective doctor-patient communication is rarely applied in practice. Limited consultation time, patient overload, doctor burnout, and poor communication skills are among the factors that cause ineffective doctor-patient communication process. This study aimed to develop a new effective communication guideline for doctor-patient communication in Indonesia by modifying the Calgary Cambridge medical interview guide. This study uses qualitative approach within four stages: expert panel, student panel and focus group discussion, expert review, and trials. Informants were chosen purposively. Three points of high category, 24 points of middle category and 44 points of low category are resulted from expert panel stage which consists of specialist representatives from 12 clinical divisions in Dr. Moehammad Hoesin central public hospital (RSMH), Palembang, South Sumatera, Indonesia. The high and middle category were discussed by two groups of internships doctors in RSMH in student panel and focus group discussion (FGD) session. The results were validated by a doctor-patient communication expert (expert reviewer) and then tested by the internship doctors through role play at the trial stage. The final result yields eight main points and eleven effective tips of the Calgary Cambridge Guide checklist modification with five to six minutes effective consultation time. This modified guideline is appropriately applicable for doctor-patient communication in daily consultation in Indonesian practical, social and cultural context.